2014
DOI: 10.1177/1089253214548764
|View full text |Cite
|
Sign up to set email alerts
|

High Thoracic Epidural in Cardiac Anesthesia

Abstract: High thoracic epidural analgesia (HTEA) offers a distinctive opportunity to enhance postoperative recovery for the thoracic surgery patient. In the modern hospital setting with day of admission surgery, the logistics of insertion of the epidural catheter has become increasingly difficult. The greatest limitation to its use might be the believed increased risk of epidural hematoma associated with anticoagulation during cardiopulmonary bypass. The aim of this review is to give an overview of complications and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 106 publications
(199 reference statements)
0
12
0
4
Order By: Relevance
“…Se han descrito otras opciones analgésicas efectivas desde un punto de vista multimodal (23,24), sin que haya suficiente evidencia para su recomendación generalizada. Se ha utilizado la analgesia epidural (25), la pregabalina (26), la oxicodona vía oral (27), la dexmedetomidina o la analgesia regional (bloqueo paravertebral (28), bloqueo intercostal o bloqueo paraesternal (29)).…”
Section: Discussionunclassified
“…Se han descrito otras opciones analgésicas efectivas desde un punto de vista multimodal (23,24), sin que haya suficiente evidencia para su recomendación generalizada. Se ha utilizado la analgesia epidural (25), la pregabalina (26), la oxicodona vía oral (27), la dexmedetomidina o la analgesia regional (bloqueo paravertebral (28), bloqueo intercostal o bloqueo paraesternal (29)).…”
Section: Discussionunclassified
“…In cardiac surgery, such fasttrack and ultra fast-track programs are not applied to all cardiac surgical procedures or to all patients. [17,[19][20][21][22][23][24][25][26] Between 2017 and 2019, publications on the results of ERAS programs in cardiac surgery increased. [6,14,19,23,[27][28][29][30][31][32][33] World leaders in the specialty recognized the need to adapt the original ERAS programs to cardiac surgery patient characteristics and to each type of intervention, and to generalize a protocol based on the best scientifi c evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies demonstrated that use of HTEA attenuated surgical stress response and thus provided hemodynamic stabilization and anti-arrhythmic effect during CABG. However, its potential complications such as epidural hematoma or abscess and procedural difficulties with epidural catheter placement and anesthetic failures have limited the use of HTEA following the initial reports [5].…”
Section: Introductionmentioning
confidence: 99%